2021
DOI: 10.3390/lubricants9050048
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Slippage and Electric Field in Mucociliary Transport of Biomagnetic Fluid

Abstract: Shear stress at the cilia wall is considered as an imperative factor that affects the efficiency of cilia beatings as it describes the momentum transfer between the fluid and the cilia. We consider a visco-inelastic Prandtl fluid in a ciliated channel under electro-osmotic pumping and the slippage effect at cilia surface. Cilia beating is responsible for the stimulation of the flow in the channel. Evenly distributed cilia tend to move in a coordinated rhythm to mobilize propulsive metachronal waves along the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…They reported that inside the microchannel, the axial flow rate is a decreasing function of the rotating Reynolds number, and the flowrate attains a steady conduct under high electroosmotic effect. Some interesting mathematical models of biological flows through microchannels are reported as an application of microfluidic pump flows [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that inside the microchannel, the axial flow rate is a decreasing function of the rotating Reynolds number, and the flowrate attains a steady conduct under high electroosmotic effect. Some interesting mathematical models of biological flows through microchannels are reported as an application of microfluidic pump flows [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…They computed the solution of modeled equations analytically via perturbation tool. Perturbation solution is computed by Munawar 6 and analyzed the phenomenon of peristaltic transport in a channel. They noticed the decrease in fluid velocity against magnetic parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash et al 10 studied the electroosmotic modulated capillary peristaltic hemodynamics that is useful in electrohydrodynamic therapy. The impact of electroosmotic flow in the microchannel with slippage is discussed by Munawar 11 . In the context of non‐Newtonian fluid, Jayavel et al 12 observed that the nanoparticle volume fraction is efficient to reduce the heat temperature of the pseudoplastic fluid.…”
Section: Introductionmentioning
confidence: 99%